2012
DOI: 10.1007/s00268-012-1545-9
|View full text |Cite
|
Sign up to set email alerts
|

Does Laparoscopic Appendectomy Impart an Advantage over Open Appendectomy in Elderly Patients?

Abstract: Laparoscopic appendectomy can be performed safely with significant advantages compared with open appendectomy in the elderly and should be considered the procedure of choice for perforated and nonperforated appendicitis in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 26 publications
3
27
0
4
Order By: Relevance
“…The overall complication rates were significantly lower in LA group as compared to open appendicectomy (OA) group (36.27 % (LA) vs. 46.92 % (OA) p<0.01) [14]. In pregnant patients undergoing LA, there is conflicting evidence with regard to increased foetal loss and preterm labour.…”
Section: Appendicitismentioning
confidence: 92%
See 1 more Smart Citation
“…The overall complication rates were significantly lower in LA group as compared to open appendicectomy (OA) group (36.27 % (LA) vs. 46.92 % (OA) p<0.01) [14]. In pregnant patients undergoing LA, there is conflicting evidence with regard to increased foetal loss and preterm labour.…”
Section: Appendicitismentioning
confidence: 92%
“…Laparoscopic appendicectomy has been found to be feasible and potentially safe in the elderly (>65 years) with no increase in morbidity [14]. The overall complication rates were significantly lower in LA group as compared to open appendicectomy (OA) group (36.27 % (LA) vs. 46.92 % (OA) p<0.01) [14].…”
Section: Appendicitismentioning
confidence: 99%
“…postoperative intestinal obstruction, nausea, vomiting, pancreatitis or complications associated with the anastomosis of the gastrointestinal tract (11% vs 9.6%) (17). Most of the complications, assessed in terms specified by the authors, occurred in patients undergoing open appendectomy surgery (9,11,13,17). The observation time in the majority of cases (6/10 works), however, did not go beyond the duration of hospitalization, which could have affected the results of the information collected due to underestimation of the number of complications and mortality.…”
Section: Surgical Treatmentmentioning
confidence: 99%
“…Operative complications, which were taken into account most frequently, were the following: surgical site infection (9,(11)(12)(13)(14)(15)17), complications of the respiratory system (9,11,12,13,15,17), urinary tract infection (9,11,13,15,17), abscesses or intra-abdominal infections (9, 11), wound dehiscence (9), acute renal failure (9,11,13), intestinal obstruction (9,11,15). In the individual studies, the most commonly observed were: wound infection (OA vs LA: 3.8% vs 1.4% (9); 5.9% vs 2.2% (13); 5.7% vs 0 (12); 8.6% vs 4.2% (14), postoperative intestinal obstruction (10.76% vs 7.3%) (11), gastrointestinal complications, i.e.…”
Section: Surgical Treatmentmentioning
confidence: 99%
See 1 more Smart Citation